1999
DOI: 10.1002/jem.44
|View full text |Cite
|
Sign up to set email alerts
|

Occupational toxic risks in dental laboratory technicians

Abstract: KEY WORDSDental laboratory technicians use a wide range of materials and techniques. They dental laboratory technician are thus subject to occupational exposures of many different kinds. The aim of occupational exposure this review is to present the circumstances of exposure, the related risks, and toxic risks the epidemiological data available in the literature. Exposures to metals, waxes, pneumoconiosis resins and silica can cause irritation or allergic reactions, affecting either the skin autoimmune disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Torbica and Krstev (2006) suggested that asbestos-related diseases in dentists might be linked to exposure to inorganic dust in the manufacturing of cobalt-chromiummolybdenum-based dental protheses. With the use of white asbestos-made lining material for casting rings in dentistry, dental technicians and dentists are potentially exposed to asbestos; and some cases of pleural plaques and malignant mesothelioma have been reported in a number of dentists after a relatively long period of work (35 to 45 years) (Choel et al, 2001;Reid et al, 1991;Sichletidis et at, 2009;Radi et al, 2002). Similarly, pneumoconiosis may occur in mechanics.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Torbica and Krstev (2006) suggested that asbestos-related diseases in dentists might be linked to exposure to inorganic dust in the manufacturing of cobalt-chromiummolybdenum-based dental protheses. With the use of white asbestos-made lining material for casting rings in dentistry, dental technicians and dentists are potentially exposed to asbestos; and some cases of pleural plaques and malignant mesothelioma have been reported in a number of dentists after a relatively long period of work (35 to 45 years) (Choel et al, 2001;Reid et al, 1991;Sichletidis et at, 2009;Radi et al, 2002). Similarly, pneumoconiosis may occur in mechanics.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Dental technicians' pneumoconiosis is a well-known clinical entity and has been described in the past [De Vuyst et al, 1986;Selden et al, 1995;Choël et al, 2001;Torbica and Krstev, 2006]. It is possible that this pneumoconiosis is caused from exposure to inorganic dust in the manufacturing of cobalt-chromium-molybdenum (CoCrMo)-based dental prostheses as well as to silica during grinding and sandblasting.…”
Section: Introductionmentioning
confidence: 99%
“…These materials may induce adverse effects such as toxicity, allergic reactions, or even cancerogenicity. Many experimental and epidemiological studies have proven the potential health hazards of metal, acrylic, and ceramic dust …”
mentioning
confidence: 99%
“…Base metal alloys typically consist of 35% to 65% cobalt, 20% to 30% chrome, 0% to 30% nickel and molybdenum, and silica, beryllium, boron, and carbon in minor quantities . Each of these metals is potentially harmful and can trigger not only allergic reactions in the skin but also various systemic diseases . Furthermore, several studies suggest that chromium, nickel, and cobalt are possibly carcinogenic to humans …”
mentioning
confidence: 99%
See 1 more Smart Citation